Engineering procedure for the certification of processes and services under regulatory requirements, for companies that manufacture and market electrical products in Colombia - Pacheco-Llanes, Sandra Milena (AiBi Journal of Research, Administration and Engineering, 2022)
An investigation was proposed with the objective of characterizing in order to standardize the procedure and the requirements for certification of processes and services under the principles of ICONTEC, for companies in the field of manufacturing and commercialization of electrical products. It was a study under the qualitative paradigm, with field and documentary design, carried out in a company in Norte de Santander dedicated to commercializing goods for the transmission and distribution of energy networks. The collection techniques were the interview with company personnel, and the documentary review of the normative and legal elements of national certification of Colombia. It concludes in the design of a procedure adapted to the company based on the regulations required by the certifying entity, in addition to the detection of important key factors of business success that mark a positive experience in the field of certification.